A review: interactions of equine herpesvirus-1 with immune system and equine lymphocyte - Nor Dini Rusli,; Khairiyah Binti Mat,; Hasnita Che Harun (2014)
Equine herpesvirus-1 (EHV-1) remains one of the most common viral pathogens affecting horses worldwide presenting as a persistent infection which can establish latency in nerve ganglia (trigeminal ganglion), lymphoid tissues of the respiratory tract and peripheral blood lymphocytes. EHV-1 infection induces both humoral and cellular immune responses in horses. Virus neutralising antibody, particularly in the nasopharynx, is to kill free virus shed from infected epithelial cells. Hence this antibody has important functions in reducing virus shedding and spreading infection to cohorts. Cellular immune responses, particularly those carried out by cytotoxic T lymphocyte (CTL), have been shown to be effective in killing virus-infected cells in vitro. This review underlines the state of knowledge regarding immunity to EHV-1 and also its interaction with equine lymphocyte. Finally, the review also includes the importance of the viral immediate early (IE) protein in the pathogenesis of EHV-1. This information can be used as the basis for future research.